Potential of Hospital Fraud in the Indonesia National Health Insurance Era (A Descriptive Phenomenological Research) - Abu Khoiri1,2 , Widi Hidayat3 , Djazuly Chalidyanto4, Fendy Suhariadi5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Results of the Public Research Anti Corruption Clearing House The Corruption Eradication Commission submitted on December 2, 2016 that until mid-2015 there was a potential of 175,774 hospital claims of fraud that had been detected with a value of Rp. 440 M. In 2016 found an indication of 1 million fictitious claims from the hospital with a value of Rp. 2 trillion. The potential for fraud in hospitals in the era of National Health Insurance (NHI) in Indonesia will have an impact on health financing inefficiencies and at the same time a threat to the sustainability of the NHI program which is expected to reach Universal Health Coverage in 2019. This phenomenological study aims to explore understanding and meaning of the concept of fraud for parties who has had the potential to commit fraud at the hospital. The research method used qualitative research with a Descriptive Phenomenology Research approach. The informants were officers who served patients in administrative and medical matters and the hospital management was selected by purposive sampling. The focus of the study was the experience felt by informants in running the NHI program and how knowledge and attitudes of informants towards the phenomenon of fraud in hospitals. The results achieved in this phenomenological research were in the form of a reflection of the implementation of NHI in hospitals, especially relating to the phenomenon of potential fraud reflected in the knowledge and attitudes of the hospital about fraud and a description of the occurrence of fraud in the hospital. This is the basis for researchers to formulate indicators of potential fraud that still needs to be tested in a larger population.